The Impact of Workaholism and Work Engagement on Distant Learning and Work-Family Conflict During the COVID-19 Lockdown - Yura Loscalzo (Amfiteatru Economic)
This study aims to analyze how workaholism and work engagement influenced Distance Learning (DL) – as a subset of teleworking, work-to-family conflict (WFC), and negative affect in Italian teachers. Moreover, among other aims, it analyzes if teachers’ perceived negative impact of DL on life influenced WFC and negative affect. Finally, it examines differences in DL-related variables concerning gender, area of living, type of school, and teacher type. A path analysis model and MANOVAs on 587 teachers (Mage = 48.80±9.17) have been performed. Among the main findings, workaholism is a positive predictor of WFC, negative affect, and DL negative impact on work and life. Work engagement, instead, is a negative predictor of these variables and a positive predictor of DL perceived efficacy. However, workaholism is a stronger predictor than work engagement. Moreover, DL negative impact on life is a positive predictor of negative affect, while DL perceived efficacy for students negatively predicts it. Finally, DL negative impact on life predicts WFC. In conclusion, this study suggests that it is imperative to reduce workaholism (and increase study engagement) to improve teachers’ well-being and work quality during DL. Moreover, Schools’ Heads should implement training to help teachers to face the technical and educational issues posed by DL (especially for teachers working in kindergarten and secondary school and with children with special needs) to make them able to provide DL of good quality. They should also provide teachers with psychological support to help them cope with the distress felt due to the changes in their work, which affected their balance between work and life (especially in primary and secondary schools)